The Effect of Perceived Quality, Perceived Value, Brand Preference, and Customer Satisfaction on ERP Implementation in Construction Services - Zainal Abidin; Athor Subroto (PT Mattawang Mediatama Solution, 2023)
Enterprise Resource Planning (ERP) is an information system in a company to optimize business processes and transactions. System Applications and Products (SAP) is one application that uses ERP system applications. The purpose of this study is to determine the effect of each variable indicating whether the system has been operating properly so that it can support maximum system performance. The research variables are Perceived Quality (PQ), Perceived Value (PV), Brand Preference (BP), dan Customer Satisfaction (CS). The data analysis method used a structural equation model or Structural Equation Model-Partial Least Square (SEM-PLS) using the SmartPLS 3.0 application. The case study used in this research is PT Hutama Karya, a construction service company. Data collection was carried out using questionnaires to 68 respondents, who are users of the SAP application with a Likert scale measurement. The result shows that PQ positively and significantly impacts on CS, PV, and BP. Brand Preference has a positive and significant influence on CS. Perceived value has a positive and significant influence on BP, but does not have a positive and insignificant effect on CS.